2000
DOI: 10.1111/j.1651-2227.2000.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial growth before and after birth: clinical implications*

Abstract: Perinatal changes in myocardial growth have recently evoked considerable interest with regard to cardiac chamber development with congenital cardiac lesions and to myocardial development in preterm infants. It is suggested that cardiac chamber development is influenced by blood flow. Experimental pulmonary stenosis in fetal lambs may induce either greatly reduced or markedly increased right ventricular volume. Ventricular enlargement appears to be associated with a large ventricular volume load resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 5 publications
3
48
0
Order By: Relevance
“…Rudolph et al reported earlier that perinatal Dex treatment inhibits or even halts physiologic myocardial hyperplasia, leaving hypertrophy as the only possibility for the still undeveloped heart to grow (30). We indeed found myocardial hypertrophy and myocardial fibrosis in the neonatally Dex-treated adult rat at 11 mo of age together with a decreased number of cardiomyocytes (18), which originated from a direct effect of neonatal Dex administration (17).…”
supporting
confidence: 48%
“…Rudolph et al reported earlier that perinatal Dex treatment inhibits or even halts physiologic myocardial hyperplasia, leaving hypertrophy as the only possibility for the still undeveloped heart to grow (30). We indeed found myocardial hypertrophy and myocardial fibrosis in the neonatally Dex-treated adult rat at 11 mo of age together with a decreased number of cardiomyocytes (18), which originated from a direct effect of neonatal Dex administration (17).…”
supporting
confidence: 48%
“…Interestingly in a recent study in our laboratory, we found that maternal protein restriction throughout pregnancy in rats leads to a reduced heart size and a concomitant decrease in the number of cardiomyocytes (5). Because cardiomyocytes in general cease proliferating soon after birth, with postnatal growth of the heart predominantly due to cardiomyocyte hypertrophy (6), these findings could have important adverse implications on the structure and function of the heart later in life. We postulate that a decrease in the total number of cardiomyocytes in neonatal hearts will limit the capacity for physiologic cardiac growth in adulthood.…”
mentioning
confidence: 98%
“…In humans, the proliferative capacity of cardiomyocytes is markedly decreased toward late gestation when the cardiomyocytes become terminally differentiated; this is characterized by myofibril assembly, sarcomeric formation and enhanced cellular contractility (Sadoshima and Izumo, 1997). Subsequent postnatal growth of the myocardium occurs by cardiomyocyte hypertrophy and/or deposition of extracellular matrix (Rudolph, 2000). In the rat heart, most cardiomyocytes are still proliferating at birth; the majority of the cardiomyocytes undergo the maturational switch during the first 2 weeks postnatally at which time they cease dividing (Li et al, 1996).…”
Section: Introductionmentioning
confidence: 99%